2016
DOI: 10.1167/iovs.16-19494
|View full text |Cite
|
Sign up to set email alerts
|

Potential Neuroprotective Effects of an LSD1 Inhibitor in Retinal Ganglion Cells via p38 MAPK Activity

Abstract: Citation: Tsutsumi T, Iwao K, Hayashi H, et al. Potential neuroprotective effects of an LSD1 inhibitor in retinal ganglion cells via p38 MAPK activity. Invest Ophthalmol Vis Sci. 2016;57:6461-6473. DOI:10.1167/ iovs.16-19494 PURPOSE. The epigenetic mechanisms associated with ocular neurodegenerative diseases remain unclear. The present study aimed to determine the role of lysine-specific demethylase 1 (LSD1), which represses transcription by removing the methyl group from methylated lysine 4 of histone H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…Loss of RGCs is a major feature of retinal excitotoxicity (Tsutsumi et al, 2016; Ishimaru et al, 2017). In the present study, NMDA-induced RGC loss was studied (7 days post-NMDA treatment) using retinal flatmount analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of RGCs is a major feature of retinal excitotoxicity (Tsutsumi et al, 2016; Ishimaru et al, 2017). In the present study, NMDA-induced RGC loss was studied (7 days post-NMDA treatment) using retinal flatmount analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Retinal excitotoxicity was induced using NMDA (N-Methyl-D-Aspartate, Sigma) according to the published methods with minor modifications (Tsutsumi et al, 2016; Ishimaru et al, 2017). Briefly, mice were anesthetized with ketamine/xylazine (73 mg/kg ketamine hydrochloride and 7.3 mg/kg xylaxine hydrochloride, i.p., intraperitoneally), pupils were dilated with 1% tropicamide (Akorn, Lake Forest, IL, United States), and topical anesthesia (1 drop of proparacaine hydrochloride, Akorn) was applied to the cornea.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Popova and colleagues21 found that Lsd1 is highly expressed in late progenitor retinal cells as they become postmitotic and begin to differentiate and that inhibition of LSD1 blocks the differentiation of the retinoblast into rod photoreceptors. Tsutsumi et al22 found potential neuroprotective effects of an LSD1 inhibitor that may protect retinal ganglion cells (RGCs), which may have implications in glaucoma. These studies have examined the effects of LSD1 inhibition in the retina, and we aimed to extend the current understanding of endogenous LSD1 expression spatially and temporally and compare and contrast our work with theirs.…”
mentioning
confidence: 99%
“…Other compounds have shown antiapoptotic effects in several animal models of ocular excitotoxicity. Between them, it is necessary to highlight I) apelin-36 and apelin-17 involved on the activation of Akt and ERK1/2 signaling pathways required for neuronal survival and inhibition of apoptosis in the retina [68], II) cannabinoids via a mechanism involving the CB1 receptors, the PI3K/Akt and MEK/ERK1/2 signaling pathways [69], III) capsaicin, a transient receptor potential vanilloid type1 agonist that activates opioid receptors, calcitonin gene-related peptide receptor and the tachykinin NK1 receptor involved in the protective effect against the NMDA receptor induced neuronal death [70], IV) pituitary adenylate cyclase-activating polypeptide through phosphatidylcholine-specific PLC pathway and cAMP production [71], V) compounds acting on adenosine A 3 receptor that attenuates the rise in calcium in RGC after activation of glutamate and P2X receptors protecting retinal cells, particularly RGC [72], VI) geranylgeranylacetone involved on the reduction in the activities of caspase-9 and -3, achieving protective results using a normal tension glaucoma mouse model which lacks GLAST [73], VII) CYM-5442 a known sphingosine 1-phosphate receptor agonist that administrated systemically in rats protected RGC from apoptotic death and preserve neuronal function after ET-1 induced RGC loss [19], VIII) adamantane derivatives such as memantine that blocks excessive activation of NMDARs without disrupting normal activity and has recently demonstrated significant preservation of RGCs density in a rodent ocular model of ocular hypertension when administrated in PLGA-polyethylene glycol (commonly PLGA-PEGylated) biodegradable nanoparticles [25], IX) tetramethylpyrazines, commonly known as TMPs, compounds able to block L-type voltage-gated calcium channels [7], X) tranylcypromine, a major lysine-specific demethylase 1 (LSD-1) and monoamine oxidase (MAO) inhibitor, that enhances expression of p38 MAPK and KEGG pathway genes [74], XI) melatonin, an autocrine or paracrine neuromodulator that regulates the local circadian physiology, that can be an effective antioxidant and antiapoptotic compound in the retina, acting as a direct and indirect free radical scavenger [75], XII) serotonin receptor (5-HT1A) agonists via the inhibition of cAMP-PKA signaling pathway that modulates GABAergic presynaptic activity [76], XIII) mTOR pathway stimulating APIs such as ciliary neurotrophic factors, lipopeptide N-fragment osteopontin mimic or lipopeptide phosphatase tension homologue inhibitors [77] or XIV) curcumin that modulates NMDA receptor subunit composition [78]. Finally, compounds with dual mechanism of action could be of special interest in multifactorial diseases as those related with RGC loss.…”
Section: Antiapoptotic Compoundsmentioning
confidence: 99%
“…[7] Tranylcypromine P38 MAPK and KEGG pathway genes expression. [74] Dual compounds (e.g., Mg acetyltaurate) NMDAR inhibition + antioxidant effect. [79] Melatonin Direct and indirect free radical scavenger.…”
Section: Compounds Pathway/mechanism Involved Bibliographymentioning
confidence: 99%